The isolation of microsatellite repeats from the human chromosome band 14q32 through inter-Alu amplification of yeast artificial chromosomes (YACs). - Bester, Aletta Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1996.